Reduced voltage stress thirteen-level extendable switched capacitor multilevel inverter - Routray A.; Shiluveru K.; Singh A.; Singh R.K.; Mahanty R. (My University, 2025)
This paper proposes a switched-capacitor multilevel inverter (SC-MLI), which ensures the peak inverse voltage (PIV) across all the switches within the dc source voltage. A total of thirteen (or higher) voltage levels can be generated using only one dc source in the proposed SC-MLI. The number of dc sources reduce significantly in the prosed circuit. In addition, voltage gain of three (or higher) is achieved through the proposed SC-MLI. As the PIV of the switches are within the input dc source voltage in the proposed SC-MLI, it requires lower rated power devices and also the total standing voltage (TSV) reduces. The capacitors in the proposed SC-MLI are self-balanced. The proposed SC-MLI has been compared with existing SC-MLIs in terms of PIV, TSV, and active/passive components in this work. The performance of the proposed 13-level SC-MLI has been validated through a 550 W experimental prototype. © 2019 IEEE.